(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines the Shortangaz Chemical Complex, located in Guzar district of Kashkadarya region, as an industrial area under climate change conditions. It discusses the analysis of results obtained from the research area to assess the fertility status of protected lands belonging to the light gray-brown sierozem soil type. Additionally, the article highlights the current relevance of soil fertility not only in agriculture but also in global food security. It also emphasizes the introduction of various practical measures within the framework of legislation in our republic.